Studi Komparatif Keefektifan Penggunaan Metode Sosiodrama Dengan Metode Ceramah Dalam Pembelajaran Bahasa Indonesia Siswa Kelas VIII Di MTs NU Umbul Sari - Sugiarti Sugiarti; Herni Fitriani (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2017)
Using the methods in learning activities is a component that must be considered by every teacher because the method affects the learning achievement to be achieved. The purpose of this study to prove the hypothesis about the comparative use of methods socio-dramas and lecturing on the subjects of Indonesian. Both methods socio-dramas and the lecture method is a method of learning which are widely applied in learning activities, including in MTs NU Bannerman Sari. This research is quantitative research. Data collection techniques used are questionnaires and documentation. The data obtained were processed and analyzed quantitatively using SPSS. The results showed (1) Application of the method socio-dramas Indonesian language study in class VIII MTs NU Bannerman Sari show the effectiveness of 92 categories of moderate or good enough, this is evidenced by the poll result mean of 82.30 in class VIII and the mean results of the questionnaire by 83 , 33 in class VIIIB.Application of a lecture on Indonesian lessons in class VIII MTs NU Bannerman Sari demonstrate the effectiveness category of moderate or good enough, this is evidenced by the poll result mean of 72.85 in class VIII and the mean results of questionnaires at 72.37 in class VIIIB.(3) There are differences in the effectiveness of the use of methods socio-dramas to use the lecture method in the Indonesian language teaching eighth grade students at MTs NU Bannerman Sari, this is evidenced by values questionnaire data is greater than t table or 13.652> 1,674 and the value of the test data greater than t table or 8.050> 1,674, meaning that the alternative hypothesis (ha) is accepted, and the null hypothesis (ho) is rejected